Discovery of Novel Thiosemicarbazides Containing 1,3,5-Triazines Derivatives as Potential Synergists against Fluconazole-Resistant Candida albicans - Fei Xie; Yumeng Hao; Jiacun Liu; Junhe Bao; Tingjunhong Ni; Yu Liu; Xiaochen Chi; Ting Wang; Shichong Yu; Yongsheng Jin; Liping Li; Dazhi Zhang; et al. (MDPI AG, 2022)
The clinical prevalence of antifungal drug resistance has been increasing over recent years, resulting in the failure of treatments. In an attempt to overcome this critical problem, we sought novel synergistic enhancers to restore the effectiveness of fluconazole against resistant Candida albicans. Based on the structural optimization of hit compound 8 from our in-house library, a series of novel 1,3,5-triazines derivatives was designed, synthesized, and biologically evaluated for synergistic activity in combination with fluconazole. Among them, compounds 10a-o, which contain thiosemicarbazides side chains, exhibited excellent in vitro synergistic antifungal potency (MIC80 = 0.125-2.0 μg/mL, FICI range from 0.127 to 0.25). Interestingly, compound 10l exhibited moderate C. albicans activity as monotherapy with an MIC80 value of 4.0 μg/mL, and also on several Cryptococcus strains (MIC80 ranging from ≤ 0.125-0.5 μg/mL) and C. glabrata (MIC80 ≤ 0.125 μg/mL). These effects were fungal-selective, with much lower levels of cytotoxicity towards human umbilical vein endothelial cells. Here, we report a series of thiosemicarbazides containing 1,3,5-triazines derivatives as potent synergists with fluconazole, and have preliminarily validated compound 10l as a promising antifungal lead for further investigation.